Deciding Framed Bisimilarity - Hüttel, Hans (BRICS Report Series, 2002)
The spi-calculus, proposed by Abadi and Gordon, is a process calculus based on the -calculus and is intended for reasoning about the behaviour of cryptographic protocols. We consider the finite-control fragment of the spi-calculus, showing it to be Turing-powerful (a result which is joint work with Josva Kleist, Uwe Nestmann, and Björn Victor.) Next, we restrict our attention to finite (non-recursive) spi-calculus. Here, we show that framed bisimilarity, an equivalence relation proposed by Abadi and Gordon, showing that it is decidable for this fragment.